2022
DOI: 10.18280/ijdne.170505
|View full text |Cite
|
Sign up to set email alerts
|

Improving Soil Fertility and Maize Growth in Suboptimal Land Through Application of Humic Acid

Abstract: Humic acid (HA) has been reported to increase plant growth and crop yields, as well as improve soil fertility. However, the potential utilization of HA extracted from various organic waste composts as organic amendment in suboptimal soils has not been studied in depth. The experiment used a two-factor Completely Randomized Design (CRD) with three replications. Four types of HA were used, namely bagasse HA (BHA), water hyacinth HA (WHA), market waste HA (MHA), and commercial HA (CHA). It also comprised of four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Total soil nitrogen is another significant nutritional indicator. It has been demonstrated that humic acid increases total soil nitrogen [42], which is in agreement with our findings. Attapulgite clay treatment enhanced total soil N, and its application with organic material boosted total soil N considerably.…”
Section: Effect Of Different Fertilization Measures On Soil Total Nit...supporting
confidence: 94%
See 1 more Smart Citation
“…Total soil nitrogen is another significant nutritional indicator. It has been demonstrated that humic acid increases total soil nitrogen [42], which is in agreement with our findings. Attapulgite clay treatment enhanced total soil N, and its application with organic material boosted total soil N considerably.…”
Section: Effect Of Different Fertilization Measures On Soil Total Nit...supporting
confidence: 94%
“…Humic acid lowered soil pH while increasing soil salinity [41][42][43], and the soil EC of organic fertilizer with humic acid slightly increased. Meanwhile, the pH of the treatment declined in the present study; a similar effect was observed in the previous study.…”
Section: Effect Of Different Fertilizer Applications On Soil Salt Con...mentioning
confidence: 98%
“…Humic acid is a kind of high-molecular-weight organic matter in nature that mainly comes from the sediment of soil, water, and plants after microbial decomposition [9,10]. Studies have shown that humic acid has good chemical properties, and the addition of humic acid to soil can regulate nitrogen transformation in the soil and reduce nitrogen migration and loss in the soil [11,12]; improve the range of phosphorus in the soil; increase the content of available nutrients and organic matter in sandy soil [13]; improve soil structure and fertility [14,15]; improve the effectiveness of trace elements in the soil [16]; and promote crop growth [17].…”
Section: Introductionmentioning
confidence: 99%